Customs Administrations in the EU Countries and Ukraine: Comparative Legal and Functional Analysis - Cherkunov, Oleksandr (Review of European and Comparative Law, 2025)
This article examines the contrasting legal status and functional roles of customs officers in the European Union and Ukraine. It highlights how the absence of law enforcement powers and procedural independence in the Ukrainian system limits the effectiveness of its customs personnel. Drawing on judicial practice and comparative models from EU member states, the study proposes concrete institutional reforms, including empowering specialized customs units with enforcement authority. These steps, it argues, are critical for aligning Ukraine’s customs administration with EU standards and strengthening its capacity to address illicit trade. In several EU member states, such as Poland and Hungary, customs authorities have an enforcement mandate, and their employees are granted a special status, which includes carrying weapons, having official titles, the right to independently investigate customs crimes, and procedural autonomy. In contrast, in Ukraine, customs officers are civil servants without law enforcement status, which limits their effectiveness in combating smuggling and customs violations. Although Ukrainian customs officials hold special ranks, this becomes an additional obstacle when it comes to pension allocation, as the Ukrainian Pension Fund does not recognize customs officers as public servants, arguing that there is no rank assigned to their public service position. The methodological framework of the study is based on comparative, formal-legal, and systemic methods. Based on the analysis of legislation, public institutions, and judicial practices, the author concludes that Ukrainian customs authorities possess low procedural autonomy and face a high level of legal uncertainty, particularly in the area of service under contract. Examples of judicial decisions provided confirm the common practice of dismissing customs officers without proper legal justification. In conclusion, the study suggests revisiting the regulatory approaches to the status of customs officers in Ukraine, taking into account European experience, particularly regarding granting law enforcement powers to specific customs units. Such a shift would strengthen the institutional capacity of the customs service and lay the groundwork for a more resilient and responsive system of financial and border security, better suited to the challenges of European integration.